Learn Intergation from Davneet Sir - Live lectures starting soon!

Ex 2.2

Ex 2.2,1
Deleted for CBSE Board 2023 Exams

Ex 2.2, 2 Important Deleted for CBSE Board 2023 Exams

Ex 2.2, 3 Deleted for CBSE Board 2023 Exams

Ex 2.2, 4 Important Deleted for CBSE Board 2023 Exams You are here

Ex 2.2, 5 Important Deleted for CBSE Board 2023 Exams

Ex 2.2, 6 Deleted for CBSE Board 2023 Exams

Ex 2.2, 7 Important Deleted for CBSE Board 2023 Exams

Ex 2.2, 8 Important Deleted for CBSE Board 2023 Exams

Ex 2.2, 9 Deleted for CBSE Board 2023 Exams

Ex 2.2, 10 Important Deleted for CBSE Board 2023 Exams

Ex 2.2, 11 Deleted for CBSE Board 2023 Exams

Ex 2.2, 12 Important Deleted for CBSE Board 2023 Exams

Ex 2.2, 13 Important Deleted for CBSE Board 2023 Exams

Ex 2.2, 14 Important Deleted for CBSE Board 2023 Exams

Ex 2.2, 15 Important Deleted for CBSE Board 2023 Exams

Ex 2.2, 16 Deleted for CBSE Board 2023 Exams

Ex 2.2, 17 Deleted for CBSE Board 2023 Exams

Ex 2.2, 18 Important Deleted for CBSE Board 2023 Exams

Ex 2.2, 19 (MCQ) Important Deleted for CBSE Board 2023 Exams

Ex 2.2, 20 (MCQ) Important Deleted for CBSE Board 2023 Exams

Ex 2.2, 21 (MCQ) Deleted for CBSE Board 2023 Exams

Chapter 2 Class 12 Inverse Trigonometric Functions

Serial order wise

Last updated at May 12, 2021 by Teachoo

Ex 2.2, 4 Prove 2tan−1 1/2 + tan−1 1/7 = tan−1 31/17 Value of 2tan−1 𝟏/𝟐 We know that 2tan−1x = tan−1 ((𝟐𝐱 )/( 𝟏 − 𝐱^𝟐 )) Replacing x with 1/2 2tan−1 1/2 = tan−1 (2 × 1/2)/(1 − (1/2)2) = tan−1 (1/(1 − 1/4)) = tan−1 (1/((4 − 1)/4)) = tan−1 (1/(3/4)) = tan−1 (𝟒/𝟑) Solving L.H.S. 2tan−1 1/2 + tan−1 1/7 Putting value of 2tan−1 1/2 = tan−1 4/3 + tan−1 1/7 = tan−1 (1/(1 − 1/4)) = tan−1 (1/((4 − 1)/4)) = tan−1 (1/(3/4)) = tan−1 (𝟒/𝟑) Solving L.H.S. 2tan−1 1/2 + tan−1 1/7 Putting value of 2tan−1 1/2 = tan−1 4/3 + tan−1 1/7 Using tan−1x + tan−1y = tan−1 ((𝒙 + 𝒚 )/( 𝟏− 𝒙𝒚)) Replacing x by 4/3 and y by 1/(7 )= tan−1 ((𝟒/𝟑 + 𝟏/𝟕 )/( 𝟏− 𝟒/𝟑 × 𝟏/𝟕)) = tan−1 (((4 × 7 +3 × 1 )/( 7 × 3) )/( (7 × 3 − 4)/(7 × 3))) = tan−1 (((28 + 3 )/( 21) )/( ( 21 − 4)/21)) = tan−1 ((31/( 21) )/(17/21)) = tan−1 (31/21×21/17) = tan−1 (𝟑𝟏/𝟏𝟕) = R.H.S. Hence, L.H.S. = R.H.S. Hence Proved